Comparative complete scheme and booster effectiveness of COVID-19 vaccines in preventing SARS-CoV-2 infections with SARS-CoV-2 Omicron (BA.1) and Delta (B.1.617.2) variants - Kislaya, Irina (2023)
Funding Information: The acquisition of sequencing equipment and reagents used in this study by the Instituto Nacional de Saúde Doutor Ricardo Jorge was partially funded by the HERA project (grant no. 2021/PHF/23776), supported by the European Commission through the European Centre for Disease Control, and also partially funded by the Genome PT project (grant no. POCI‐01‐0145‐FEDER‐022184), supported by COMPETE 2020–Operational Programme for Competitiveness and Internationalisation, Lisboa Portugal Regional Operational Programme, Algarve Portugal Regional Operational, under the Portugal 2020 Partnership Agreement, through the European Regional Development Fund, and by the Portuguese Science and Technology Foundation. The Algarve Biomedical Center Laboratory received public funding through the Project ALG‐D2‐2021‐06 Variants Screen in Southern Portugal–Monitoring Variants of Concern in Southern Portugal and the Portuguese Science and Technology Foundation national support through the Comprehensive Health Research Center (grant no. UIDP/04923/2020). Funding information Funding Information: The acquisition of sequencing equipment and reagents used in this study by the Instituto Nacional de Saúde Doutor Ricardo Jorge was partially funded by the HERA project (grant no. 2021/PHF/23776), supported by the European Commission through the European Centre for Disease Control, and also partially funded by the Genome PT project (grant no. POCI-01-0145-FEDER-022184), supported by COMPETE 2020–Operational Programme for Competitiveness and Internationalisation, Lisboa Portugal Regional Operational Programme, Algarve Portugal Regional Operational, under the Portugal 2020 Partnership Agreement, through the European Regional Development Fund, and by the Portuguese Science and Technology Foundation. The Algarve Biomedical Center Laboratory received public funding through the Project ALG-D2-2021-06 Variants Screen in Southern Portugal–Monitoring Variants of Concern in Southern Portugal and the Portuguese Science and Technology Foundation national support through the Comprehensive Health Research Center (grant no. UIDP/04923/2020). Publisher Copyright: © 2023 The Authors. Influenza and Other Respiratory Viruses published by John Wiley & Sons Ltd.